52.8k views
0 votes
Solve for the variable c in this equation.
a(c + b) = d

Solve for the variable c in this equation. a(c + b) = d-example-1

2 Answers

3 votes

Steps to solve:

a(c + b) = d

~Distribute

ac + ab = d

~Subtract ab to both sides

ac + ab - ab = d - ab

~Simplify

ac = d - ab

~Divide a to both sides

ac/a = d-ab/a

~Simplify

c = d-ab/a

Therefore, the answer is A

Best of Luck!

User AlbinoDrought
by
6.0k points
3 votes

Answer:

c = (d-ba) /a

Explanation:

a(c + b) = d

Divide each side by a

a/a(c + b) = d/a

c+b = d/a

Subtract b

c = d/a -b

Get a common denominator

c =d/a - ba/a

c = (d-ba) /a

User Pradeeptp
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.